Strategies for Teaching Islamic Education in the Context of Multicultural Education - Lailika Nurrahman Amelia Aisya Putri; Yulia Nurrahmasari; Sholikhatul Amalia; Putri Rodhiyatul Laili; Abd. Rozaq (Atthiflah: Journal of Early Childhood Islamic Education, 2025)
The diversity of students’ religions, cultures and social backgrounds in state schools requires teaching strategies capable of instilling the values of tolerance and respect for differences. This study aims to analyse the teaching strategies used in Islamic Religious Education (PAI) in the implementation of multicultural education, as well as the stages of its evaluation at SMP Negeri 1 Gudo. The study employs a qualitative approach using a case study design. Data were collected through interviews, observations and documentation, and subsequently analysed using the interactive model developed by Miles, Huberman and Saldaña. The results indicate that the implementation of multicultural education is carried out through inclusive learning by providing non-Muslim pupils with the opportunity to participate in PAI lessons, the use of methods such as lectures, discussions and question-and-answer sessions, and the utilisation of muamalah materials that incorporate values of interpersonal relationships, consultation and mutual cooperation. Learning evaluation is conducted through the assessment of cognitive, affective and psychomotor aspects. These findings indicate that PAI lessons can serve as a means of internalising multicultural values without undermining pupils’ religious identities. In practical terms, the results of this study can serve as a reference for schools with a diverse pupil body in developing inclusive religious education. As this study was limited to a single research site, further research in different contexts is required